Ramification of crowdfunding on Bangladeshi entrepreneur’s self-efficacy - Zainudin, Awang; Habsah, Muda; Fauzilah, Salleh (2018)
The novel funding sources turn out to be important for the Small and Medium Enterprises (SMEs) sector all over the world especially after 2007-2008 world financial crisis. Thus, to develop a new business idea and start-ups, SMEs need a sufficient amount of capital. However, after the financial crisis in 2008, SME sector faced the challenges of attracting new capital. Therefore, an innovative method of fundraising for SME was introduced as crowdfunding. Crowdfunding indicates financing a project or an idea via the internet owing the help from the many investors or donors of a society. Since there are limited works about the influence of Crowdfunding on Entrepreneur Self-efficacy (ESE), hence, to minimize the research gap and to achieve the objective of the study, we conduct a quantitative research among 190 entrepreneurs in Bangladesh using crowdfunding based on Social Cognitive theory. The data were analyzed using Structural Equation Modeling (SEM) in IBM-SPSS-Amos 25.0 and the stated hypotheses were tested. The study found a direct and positive effect of Crowdfunding on Entrepreneur’s Self-efficacy (β=0.924, P=.001). Overall, the result has landed support for crowdfunding, which indicates that it can influence on self-efficacy of entrepreneur. In order to determine the need of crowdfunding, we have explained and statistically demonstrated how crowdfunding can provide a supplementary channel where firms can gain finance and to create self-efficacy of entrepreneurs through exploiting the potential of internet.